Quality assessment of medicinal plant Enicostemma littorale, Bluyme by physic phytochemical analysis - Vinotha, S.; Ira, T.; Sri Ranjani, S. (Gampaha Wickramarachchi Ayurveda Institute, University of Kelaniya, 2012)
Enicostemma littorale, Blume (Gentiananceae) also called Vellarugu in Tamil, Indian gentian, in English, Mamajaka in Sanskrit and Naahi in Ayurveda is a glabrous perennial herb which grows up to a height of 1.5ft is found throughout India. In Sri Lanka, it is found in open, sandy places among sparse grass close the beach throughout the dry zone particularly from northwestern to northeastern coastal belt. It is traditionally used to treat (a) inflammatory and painful conditions like arthritis, back pain, (b) diabetes mellitus, and (c) to regulate bowel functions. The objective of this study was to evaluate the physicochemical and phytochemical constituents of the E. Littorale. Six samples of whole plant powder of E. Littorale were standardized according to the methods recommended by the World Health Organization (WHO). In the present study, the physicochemical parameters such as loss on drying, ash values, pH value, aqueous, and alcoholic extractive values were calculated. Preliminary phytochemical screening was carried out to ascertain the quality of this plant. All samples were tested and mean values along with standard deviation were recorded. The results showed that it contains loss on drying 10.25±0.33%, ash values (total ash 8.16±0.1%, water soluble ash 2.75±0.1%, acid insoluble ash 1.89±0.1%, and sulfated ash 1.30±0.1%) and pH value 5.12±0.02. The solubility percentage of E. Littorale in aqueous hot extraction is higher (37.21±1.27%), when compared with ethanolic hot extraction (24.92±0.64%). The phytochemical screening of hot aqueous and ethanolic extracts indicated the presence of Alkaloids, saponins, flavonoids, steroids, tannins, proteins, quinines, reducing sugar and coumarins, and does not indicate the presence of anthraquinones. The generated information of the present study will provide data which is helpful in the correct identification and authentication of this medicinal plant.
Keywords: Enicostemma littorale; Vellarugu; Physicochemical; Phytochemical; Evaluation